[Wrzeszcz, dworek Jaśkowa Dolina 9] [aut. odb. Karol Nowaliński]. - Nowaliński, Karol (1935- ). (Karol Nowaliński, 1986)
Przedstawia dwór z XVIII w. przy ul. Jaśkowa Dolina (Jäschkentaler Weg) 9, ok. 1905 r.